Extraction and long‐term storage of S‐layer proteins and flagella from Lysinibacillus sphaericus NCTC 9602: Building blocks for nanotechnology. Issue 4 (5th March 2015) - Blüher, Anja; Ostermann, Kai; Jäckel, Petra; Clemens, Andrè; Katzschner, Beate; Rödel, Gerhard; Mertig, Michael
<x xml:space="preserve">Abstract</x> Self‐assembling surface layer (SL) proteins of bacteria have been widely studied, in particular their use as molecularly defined, 2D coatings of technical surfaces. An important prerequisite is the availability of a sufficient amount of protein. However, a detailed and optimized protocol for the complete SL extraction is so far not available. Here, we describe the complete purification and reassembly procedure of an SL protein of Lysinibacillus sphaericus NCTC 9602, starting from the cultivation of cells, the preparation and purification of SL proteins up to the long‐term storage and in vitro self‐assembly of the proteins. All crucial steps of the procedure are assessed by different microscopic techniques, such as light microscopy, atomic force microscopy, and scanning electron microscopy as well as by SDS‐PAGE as a biochemical method. We demonstrate that storage of the protein in the presence of sodium azide or upon lyophilization allows the preservation of the self‐assembly properties for at least 9 years. Additionally, we describe a method allowing the extraction of intact flagella with lengths in the range up to 4 μm. Flagella may have applications in bio‐nanotechnology, for example as templates for metallic nanowires.